A Study on Quality of Work Life of Employees in LPG Bottling Plant - T. S. Nanjundeswaraswamy; Swamy Devappa Renuka; Rashmi Srinivasaiah (Brazilian Journal of Operations & Production Management, 2021)
Goal: Quality of Work Life (QWL) draws more attention in the present context, and it is a multidimensional construct. The oil and gas industries have realized the significance of employees' QWL to retain and attract a talented workforce in the competitive job market. This study examines the status of QWL of employees in the LPG Bottling Industry.